IoT Based Smart Pet Cage - Pulainthran, Thineswari; Jais Bin Lias, (Evolution in Electrical and Electronic Engineering, 2022)
In this modern era, there is a lot of technological improvement in pet cages. The world is moving rapidly toward automated or smart mechanisms. The manual operation of pet cages may not be efficient for the modern world. Pet ownership is a wonderful experience that everyone should enjoy at least once in their lives. Pets are, without a doubt, animals. A pet is a companion as well as a sentient being. True, caring for a pet and ensuring that they remain healthy is a difficult responsibility, but with the appropriate information, it may be made a little easier. The owners worry about their pet’s food consumption and its safety. There is a high chance that the food will get spoiled if left outside for a long time. This cage can sense the difference in temperature in the surrounding. A temperature sensor is added to this project for to detect the changes in the surrounding temperature. If the sensor senses the level of the temperature exceeded more than required, a notification will be sent to the owner and the cage gate will be open so that the pet can go to a safer place. A weight sensor is added to this project for feeding purposes based on a required weight. The feeding system in this cage also can dispense food accordingly based on its weight automatically. A water level sensor is also added to feed water for the pet. If the water level goes below than required level the water will start pumping the water into the feeder bottle automatically. IoT system is built in this project to operate manually the cage which allows the owner to open/close the cage manually.  The simple cage was successfully built to set up the device into it so that it would make the testing process easier for result purposes.